Method for detecting threshing degree of roughened layer on surface of rolled copper foil

By applying an adhesion layer to the surface of rolled copper foil and performing colorimetric quantitative detection, the problem of rapid and accurate quantitative detection of the degree of degranulation of the roughened layer on the surface of rolled copper foil was solved, ensuring the adhesion strength between the copper foil and the circuit board carrier and avoiding the risk of circuit detachment and short circuit.

CN120948371APending Publication Date: 2025-11-14ANHUI ZHONGYUAN COPPER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511166158.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-20
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing technologies lack a rapid, accurate, and quantitative method to detect the degree of delamination of the roughened layer on the surface of rolled copper foil. This makes it difficult to detect plating delamination problems in a timely manner, affecting the adhesion strength between the copper foil and the circuit board carrier, and potentially leading to problems such as circuit detachment and short circuits.

Method used

The weakly bonded particles were triggered to detach by applying a preset pressure using an adhesive layer (such as tape with a peel force of 0.1-1.0N/25mm and a light transmittance of ≥90%). The degree of detachment was quantified by the degree of color development. Colorimetric comparison was performed using a standard color chart. Color changes were measured using a spectrophotometer and observed on a white substrate.

Benefits of technology

It enables rapid, simple, and quantitative threshing detection, reduces operational skill requirements, lowers detection costs, improves detection efficiency, provides reliable quality control data, and can promptly detect and address threshing problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120948371A_ABST
    Figure CN120948371A_ABST
Patent Text Reader

Abstract

The invention provides a rolled copper foil surface roughening layer threshing degree detection method, and relates to the technical field of electronic material detection, and the method comprises the following steps: applying an adhesion layer on a roughening surface of a rolled copper foil; applying preset pressure to trigger separation of the weak binding particles; stripping the transfer adhesive layer to the white substrate; the threshing severity is quantified through the color development degree; according to the method, the whole detection process is few in steps, professional technicians do not need to carry out complex operation training, common detection personnel can rapidly grasp the method, the skill requirement for operators is reduced, adhesive tapes, white paperboards, round bars and other consumables used in the detection process are common articles and are easy to purchase in the market, the cost is low, the detection cost is reduced, and the method is suitable for popularization and application. The whole process from sample preparation to detection result obtaining is short in time consumption, the requirement for rapid detection of a production line can be met, the product quality detection efficiency is improved, and problems can be found in time and measures can be taken.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic material testing technology, and in particular to a method for detecting the degree of degranulation of the roughening layer on the surface of rolled copper foil. Background Technology

[0002] Rolled copper foil, a core raw material in flexible circuit boards (PCBs) used in electronic products, directly affects the performance and lifespan of the PCBs. Rolled copper foil uses rolled copper as a base material and undergoes an electroplating process to deposit a layer of fine copper particles and other corrosion-resistant and high-temperature-resistant metal particles on its surface, forming a roughening layer. The key function of this roughening layer is to increase the adhesion strength between the copper foil surface and the PI film on the PCB substrate, effectively preventing copper circuits from detaching or short-circuiting, thus ensuring the stable operation of electronic products.

[0003] However, in actual production, the roughening layer of rolled copper foil is highly susceptible to various factors. Fluctuations in plating bath temperature, changes in plating bath concentration, unstable current density, and deviations in plating time during the electroplating process can all lead to weak bonding between the plating particles and the substrate. This phenomenon is known in the industry as "plating particle delamination." Plating particle delamination is extremely harmful, severely reducing the adhesion strength between the copper foil and the PI film on the circuit board carrier. Copper foil with severe surface delamination, when applied to circuit boards, is highly prone to serious problems such as circuit detachment and short circuits during the use of electronic products. This not only causes huge economic losses to downstream manufacturers but may also lead to safety accidents, threatening the lives and property of users. Currently, the industry lacks a fast, accurate, and quantifiable effective solution for detecting the adhesion of plating particles on rolled copper foil. Existing detection methods are either complex and time-consuming, unsuitable for the rapid testing needs of production lines, and the results are highly subjective, difficult to quantify, and cannot provide a reliable basis for product quality control. Therefore, this invention proposes a method for detecting the degree of particle delamination in the surface roughening layer of rolled copper foil to solve the problems existing in the prior art. Summary of the Invention

[0004] To address the aforementioned problems, this invention proposes a method for detecting the degree of de-granulation of the roughened layer on the surface of rolled copper foil. This method is simple to operate, uses readily available consumables, and is quick and convenient to use. Furthermore, it can clearly determine the degree of de-granulation of the roughened surface of the copper foil by observing the degree of color change, thus providing a highly intuitive and quantitative assessment of the de-granulation test results.

[0005] To achieve the objective of this invention, the invention is implemented through the following technical solution: a method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil, comprising the following steps: S1: Apply an adhesion layer to the roughened surface of the rolled copper foil; S2: Applying a preset pressure triggers the detachment of weakly bound particles; S3: Peel off the transfer adhesive layer to the white substrate; S4: Quantify the severity of threshing by the degree of color development.

[0006] A further improvement is made in S1, where, before applying the adhesion layer, the roughened surface of the rolled copper foil is purged with an inert gas to remove free particles.

[0007] A further improvement is that, in S1, the adhesive layer is a tape with a peel force of 0.1-1.0 N / 25 mm and a light transmittance of ≥90%.

[0008] A further improvement is that, in S2, the preset pressure is achieved by a linear pressure of 5-100 g / cm², and the pressure application device includes a round bar, a pressure roller, or a flat pressure head.

[0009] A further improvement is that the pressure application device is a metal round bar with a diameter of 5-20mm, a rolling speed of 5-20mm / s, and a rolling cycle of 1-5 times.

[0010] A further improvement is made in S3, where the tape is slowly peeled off at a 180° angle from the surface of the rolled copper foil, with the peeling speed controlled at 10-20 mm / s.

[0011] A further improvement is that the peeled tape is immediately adhered to the surface of a white substrate, which is a pure white cardboard surface with a whiteness of ≥90%.

[0012] A further improvement is made in S4, where the quantification of color rendering includes the following steps: Establish a standard color chart, which contains N color levels, N≥3, and each color level corresponds to a different threshing quality threshold. The test sample is compared with the standard color chart in terms of colorimetric properties.

[0013] A further improvement is made by establishing the standard color chart through the following steps: Prepare a benchmark sample set with known threshing degrees; The mass m of detached particles from the reference sample and the color difference ΔE in the color development area were measured. Construct m-ΔE calibration curves to classify threshing grades.

[0014] Further improvements include: colorimetric comparison is performed using a spectrophotometer, with the measurement area being a 5×5mm² area at the center of the adhesion layer, and the average value of three measurements is taken.

[0015] The beneficial effects of this invention are as follows: 1. The entire testing process of this invention has few steps and does not require complex operation training for professional technicians. Ordinary testing personnel can quickly master it, which reduces the skill requirements for operators. The consumables used in the testing process, such as tape, white cardstock, and round rods, are all common items that are easy to purchase on the market and are inexpensive, thus reducing testing costs.

[0016] 2. The entire process from sample preparation to obtaining test results is short, which can meet the needs of rapid testing on the production line, improve the efficiency of product quality testing, help to identify problems in a timely manner and take measures. The degree of threshing is reflected by the degree of tape color change. After comparison with the standard color card, the threshing test results can be intuitively and quantitatively evaluated, avoiding the problem of strong subjectivity in the results of traditional testing methods, and providing a reliable basis for product quality control. Attached Figure Description

[0017] Figure 1 This is a flowchart of the present invention. Detailed Implementation

[0018] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention. Example 1

[0019] according to Figure 1 As shown in the figure, this embodiment proposes a method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil, including the following steps: S1: Apply an adhesive layer to the roughened surface of the rolled copper foil; before applying the adhesive layer, purge the roughened surface of the rolled copper foil with inert gas to remove free particles; the adhesive layer is a tape with a peel strength of 0.1-1.0 N / 25 mm and a light transmittance of ≥90%; S2: Apply a preset pressure to trigger the detachment of weakly bonded particles; the preset pressure is achieved by a linear pressure of 5-100 g / cm², and the pressure application device includes a round bar, a pressure roller, or a flat pressure head; the pressure application device is a metal round bar with a diameter of 5-20 mm, a rolling speed of 5-20 mm / s, and 1-5 rolling cycles; S3: Peel off the transfer adhesive layer to the white substrate; when peeling off the tape, slowly tear it away from the surface of the calendered copper foil at a 180° angle, with the peeling speed controlled at 10-20mm / s; immediately stick the peeled tape to the surface of the white substrate, which is a pure white cardboard surface with a whiteness ≥90%; S4: Quantifying the severity of threshing by color development. Color development quantification includes the following steps: establishing a standard color chart containing N color levels, where N≥3, with each color level corresponding to a different threshing quality threshold; comparing the colorimetric values ​​of the test samples with the standard color chart. The standard color chart is established through the following steps: preparing a reference sample set with known threshing degrees; measuring the mass of detached particles m and the color difference ΔE between the color development area and the reference sample; constructing an m-ΔE calibration curve to classify threshing levels. Colorimetric comparison is performed using a spectrophotometer, with the measurement area being a 5×5mm² area at the center of the adhesion layer, and the average of three measurements is taken. Example 2

[0020] according to Figure 1 As shown in the figure, this embodiment proposes a method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil, including the following steps: Sample preparation: Take a piece of ultra-thin rolled copper foil with a thickness of 9μm and lay it flat on a flat sample stage with a silicone pad, roughened side up. Use tweezers to gently place the sample to avoid wrinkles or damage.

[0021] Tape application and rolling: Gently apply a 1cm wide, non-adhesive, high-transparency tape to the center area of ​​the roughened surface of the copper foil. Roll it twice evenly with a 50g round rod at a speed of 2cm / s. Use a suspended operation during rolling to avoid applying additional pressure. Tape peeling: After the tape has been adhered and stabilized for 15 seconds, hold one end of the tape with tweezers and peel it slowly at a speed of 1 cm / s along a direction parallel to the copper foil surface. Keep the tweezers stable and do not shake during the peeling process. Color observation and judgment: After peeling off the tape, stick it flat on a pure white card and observe the color of the tape under natural light. Compare it with the standard color card to determine the degree of delamination. Example 3

[0022] according to Figure 1 As shown in the figure, this embodiment proposes a method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil, including the following steps: Sample preparation: Take a piece of rolled copper foil sample that has been repeatedly bent 50 times at 180°, lay it flat on a flat sample stage with the roughened side facing up, and conduct the test after observing that there is no obvious breakage in the bending area.

[0023] Tape application and rolling: Apply 2cm wide, non-adhesive, high-transparency tape to the bent and non-bent areas of the sample respectively, and roll each area 3 times with a 50g round rod at a speed of 4cm / s to ensure that the tape is fully adhered to both areas.

[0024] Tape peeling: After the tape has been firmly bonded for 10 seconds, peel off the tape from the two areas at the same speed and angle, and mark the areas accordingly.

[0025] Color observation and judgment: Paste the tape of the two areas on the corresponding positions of the white card, compare the color difference between the two, and compare them with the standard color card to evaluate the effect of bending on the threshing performance of the roughened layer.

[0026] Validation data:

[0027] As can be seen from the above data, the detection method of the present invention can effectively distinguish the degree of threshing of different samples and regions, and the detection results are consistent with the actual threshing situation, thus demonstrating reliability.

[0028] This method for detecting the degree of de-granulation on the surface roughening layer of rolled copper foil involves a few steps and requires no complex training for specialized technicians. Ordinary inspectors can quickly master the process, reducing the skill requirements for operators. The consumables used in the testing process, such as tape, white cardstock, and round rods, are common items, readily available on the market, and inexpensive, thus lowering testing costs. Furthermore, the entire process from sample preparation to obtaining test results is time-efficient, meeting the needs of rapid testing on production lines, improving product quality testing efficiency, and facilitating timely problem detection and corrective action. The degree of de-granulation is reflected by the degree of tape color change, and comparison with a standard color chart allows for a direct and quantitative evaluation of the de-granulation test results, avoiding the subjectivity of traditional testing methods and providing a reliable basis for product quality control.

[0029] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil, characterized in that, Includes the following steps: S1: Apply an adhesion layer to the roughened surface of the rolled copper foil; S2: Applying a preset pressure triggers the detachment of weakly bound particles; S3: Peel off the transfer adhesive layer to the white substrate; S4: Quantify the severity of threshing by the degree of color development.

2. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 1, characterized in that: In step S1, before applying the adhesion layer, the roughened surface of the rolled copper foil is purged with inert gas to remove free particles.

3. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 2, characterized in that: In S1, the adhesive layer is an adhesive tape with a peel strength of 0.1-1.0 N / 25 mm and a light transmittance of ≥90%.

4. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 1, characterized in that: In S2, the preset pressure is achieved by a linear pressure of 5-100 g / cm², and the pressure application device includes a round bar, a pressure roller, or a flat pressure head.

5. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 4, characterized in that: The pressure application device is a metal round bar with a diameter of 5-20mm, a rolling speed of 5-20mm / s, and a rolling cycle of 1-5 times.

6. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 1, characterized in that: In step S3, the tape is slowly peeled off at a 180° angle from the surface of the rolled copper foil, with the peeling speed controlled at 10-20 mm / s.

7. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 6, characterized in that: The peeled tape is immediately adhered to the surface of a white substrate, which is a pure white cardboard surface with a whiteness of ≥90%.

8. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 1, characterized in that: In step S4, the quantification of color rendering includes the following steps: Establish a standard color chart, which contains N color levels, N≥3, and each color level corresponds to a different threshing quality threshold. The test sample is compared with the standard color chart in terms of colorimetric properties.

9. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 8, characterized in that: The standard color chart is established through the following steps: Prepare a benchmark sample set with known threshing degrees; The mass m of detached particles from the reference sample and the color difference ΔE in the color development area were measured. Construct m-ΔE calibration curves to classify threshing grades.

10. The method for detecting the degree of de-granulation of the roughening layer on the surface of rolled copper foil according to claim 9, characterized in that: Colorimetric comparison was performed using a spectrophotometer. The measurement area was 5×5mm² at the center of the adhesive layer, and the average value of three measurements was taken.